(untitled) (Medico Legal Update, 2021)
The focus of this research study is the law on the distribution of joint assets and child custody as a result of divorce against husbands and wives who work based on justice value. Article 97 Compilation of Islamic Law which determines that widows of divorced widows get a half share of the joint property. This is inseparable from the provisions of Article 31 and Article 34 of Law Number 1 of 1974 concerning Marriage. This study uses normative juridical method, sociological juridical method, and comparative juridical research method; and using decision data and interviews with judges of the religious courts, using critical paradigms and using inductive qualitative analysis. The results of the study were that the judge had begun to make legal discoveries. Factors that influence the ruling of the religious courts that do not bring about justice are substantial, structural, and cultural factors. The current division of shared assets and the rights of child ownership as a result of divorce is not yet fair, meaning that the construction of the distribution of shared assets and child rights as a result of divorce is currently granted by The reconstruction of the legal value of the distribution of shared assets due to divorce is carried out casually based on its contribution by taking into account the benefit and well-being of the company.